Piezo step to a brighter future - Danseco, Joselito E. Jr; De Leon, Diwata D.; Sta. Maria, Kevin Michael A.; Suarez, Olivia Graciela V.
The Piezo is a floor tile that generates renewable energy through the harvesting and conversion of mechanical energy from foot strikes through the piezoelectric effect. The product utilizes a lead zirconate titanate (PZT) composite bimorph that triggers the creation of energy under the oscillating pressure of foot strikes. This system produces 0.57 Wh per step on a 1 x 1 square feet of tile for an average 120-lb individual. Considering the effectiveness of the product, maximum energy generation can then be achieved by installing the Piezo in areas with considerably high foot traffic. These commercial establishments are considered the target market segment of the product which includes local malls, train stations, disco bars, dance studios, and airport terminals. Total cost of ownership for the Piezo amounts to PhP 5,000 which includes pre-sales services of traffic counting, product cost, installation, monthly checkup and repair, and parts and services warranty for 6 years. Piezo Innovations Co., the manufacturer and seller of Piezo, provides a breakthrough technology in renewable energy generation in the Philippines as a response to the anticipated increase in energy prices and fluctuations in energy supply. In this feasibility study, the production of the Piezo is analyzed with respect to its market, technical, organizational, financial and socio-economic feasibility. Studying these aspects of the product, the Piezo is deemed not only feasible but also beneficial to its future investors, customers, to the environment and to the country.